THE EFFECT OF TRUST AND RISK PERCEPTIONS USING E-COMMERCE ON CONSUMER PURCHASE INTENTIONS - Inggrie Septiani (Marketgram Journal, 2023)
The purpose of this study is to determine the effect of trust and risk perceptions using ecommerce on consumer purchase intentions on the Lazada site (Study on Lazada consumers in Sukabumi City) Methodology: The research method used is a survey method using a questionnaire distributed to 100 samples. While the instrument quality testing technique includes validity and reliability tests. The classical assumption test technique uses the normality test, multicollinearity test, and heteroscedasticity test. Meanwhile, to test the hypothesis using multiple linear regression analysis, t test (partial), and f test (simultaneous). Results: That the trust variable has a significant effect on the intention of the client. Meanwhile, the Risk Perception variable has no effect on Purchase Intention. partially and there is a significant influence between Trust and Risk perception on Purchase Intention.